The Impact of Service Quality and Product Attributes on Customer Satisfaction in Islamic Finance - Noviarita , Heni; Anggriani , Jum; Hilal , Syamsul; ., Madnasir; Ekawati , Evi (Journal of Ecohumanism, 2024)
This study investigates the impact of service quality and product attributes on customer satisfaction within the context of Islamic finance. Utilizing a quantitative approach, data were collected from 500 customers across various Islamic banking institutions. The findings reveal that both service quality and product attributes significantly influence customer satisfaction, with service quality demonstrating a stronger correlation. Notably, aspects such as employee friendliness, responsiveness, and product diversity emerged as critical factors. This research contributes to the existing literature by providing empirical evidence on the importance of service quality in enhancing customer satisfaction specifically in the Islamic banking sector, an area that has received limited attention. The implications of this study are twofold: first, it offers valuable insights for Islamic banking institutions to refine their service delivery and product offerings, thereby fostering greater customer loyalty. Second, it highlights the need for continuous assessment of customer expectations and satisfaction metrics to ensure sustainable growth in the competitive financial landscape. This study lays the groundwork for future research on the interplay between service quality, product attributes, and customer satisfaction in Islamic finance.